2020
DOI: 10.33225/jbse/20.19.1078
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 as an Agent of Change in Teaching and Learning Stem Subjects

Abstract: The closing of schools due to Covid-19 has brought a dimension of uncertainty into STEM education. Despite the closing of schools due to the need to observe physical distancing, some schools have found ways to continue teaching and learning on virtual platforms enabled by increasingly pervasive fourth industrial revolution environments. In this study, the teaching of Ordinary level mathematics and science in pursuit of STEM education goals as enabled by the Internet of Things (IoT) in online classrooms was the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…On the other hand, as several studies mentioned, technology and engineering students have been seriously affected by the distance education that inhibited the practice and the use of specific technological tools (Arroio, 2020;Asgari et al, 2021;Makamure & Tsakeni, 2020). For lecturers, distance teaching/learning proved confusing, which slightly reduced the quality of teaching compared to the regular type of study (Rizun & Strzelecki, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, as several studies mentioned, technology and engineering students have been seriously affected by the distance education that inhibited the practice and the use of specific technological tools (Arroio, 2020;Asgari et al, 2021;Makamure & Tsakeni, 2020). For lecturers, distance teaching/learning proved confusing, which slightly reduced the quality of teaching compared to the regular type of study (Rizun & Strzelecki, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The university LMS had to be complemented by a social media platform that was easily available and cheap in the transition to online learning. Social media platforms play a significant role in building online classrooms (Saadatmand et al 2017;Makamure & Tsakeni, 2020). Therefore, the teaching presence was established mainly through recorded material posted on the LMS and the social media platform for the preservice to download at a convenient time when they connected their devices to the internet from both the LMS and WhatsApp.…”
Section: Discussionmentioning
confidence: 99%
“…LMSs and Web 2.0 tools such as social media and web-based office tools such as Google and Microsoft are some of the IoT-enabled technologies used to build online learning ecosystems (Scott et al, 2016). Makamure and Tsakeni (2020) observed that the WhatsApp social media platform played a significant role in building online classrooms during the COVID-19 pandemic. The advent of online learning has also influenced teacher education.…”
Section: Internet Of Things and Online Learningmentioning
confidence: 99%
“…In Makamure and Tsakeni [13], ordinary level mathematics and science teaching was investigated in line with the STEM education goals provided by the Internet of Things in online classrooms. As a result, it was concluded that teachers revealed their experience with this transition and that they chose specific Web 2.0 tools to create online classrooms.…”
Section: Related Researchmentioning
confidence: 99%